- 1-800-665-6601
- [email protected]

Here each square root radical should be simplified further.

√40 = √(2* 2* 2* 5). Now pull out the number which is repeating twice inside the radical.

This gives:

So, √40 + √250 = 2√10 + 5√10 = (2 + 5) √10 = 7√10.

(They are like terms since they have the same radical √10 and hence can be added).

Hence the value of the expression, √40 + √250 is = 7√10.

Here each square root radical should be simplified further.

√10 = √(2* 5)and it is already in its simplified form as no number is repeating twice inside the radical to be pulled out.

And we have

So, √250 - √10 = 5√10 -1√10 = (5 – 1) √10 = 4√10.

(They are like terms since they have the same radical √10 and hence can be added).

Hence the value of the expression, √250- √10 is = 4√10.